The value of fecal calprotectin in Clostridioides difficile infection: A systematic review - Wen, Bao-Jiang; Te, Li-Ger; Liu, Xiao-Xuan; Zhao, Jian-Hong (Frontiers in Physiology, 2022)
As a marker of inflammation, calprotectin has potential application value in a variety of inflammatory diseases, such as arthritis and bacterial infections. Clostridioides difficile infection (CDI) is an infectious disease that causes intestinal damage and inflammation. This systematic review aims to determine whether fecal calprotectin has application value in CDI. Nine databases were searched from inception to 6 June 2022, and 17 studies were included. These studies were divided into four groups according to their content. Generally speaking, fecal calprotectin is not an ideal indicator for the diagnosis and prognosis prediction of CDI but may serve as a potential indicator for assessing disease severity and as a readily detectable marker for CDI screening.In addition, patients in need of treatment or with detectable toxins in stool may tend to have higher levels of fecal calprotectin. In summary, fecal calprotectin has some potential application value in CDI. However, further studies are needed to verify these findings and determine the reliability of calprotectin as a biomarker for CDI.